Quality Control Analysis to Reduce Instant Noodle Product Defects with Six Sigma and Kaizen Method - Isna Nugraha; Dwi Sukma Donoriyanto (Future Science, 2023)
PT. XYZ is a company operating in the food industry, with its main product being instant noodles. In its production process, not all products produced meet the quality standards set by the company. This indicates the presence of defective products, often due to errors in factors such as machinery or human resources, among others. Initial observations reveal that there are still many defects in their products. Quality control at PT. XYZ is done manually by the owner, who supervises each production cycle. Defects in PT. XYZ's products are categorized into three types: torn noodle packaging, crushed noodles, and torn seasoning packaging. Therefore, improvements are needed in the production of instant noodles by PT. XYZ. This research aims to improve the quality of production in the company and to explain the approach to analyzing the defect rate of instant noodles using Six Sigma and Kaizen. The results obtained using the Six Sigma method in the DMAIC analysis (Define, Measure, Analyze, Improve, Control), showed that product quality testing during the instant noodle production process resulted in 3238 failures. The Defects Per Million Opportunities (DPMO) value was 41172.88, which, when converted to a sigma level, was 3.23, indicating that the sigma level was at the industry average in Indonesia. This suggests that there is a potential for 41172.88 defects per one million productions, showing an inconsistent pattern of DPMO and sigma achievement. This indicates that the production process has not been managed accurately and requires improvement, particularly in the quest for zero defects.